Core components of the international forest regime complex - Angelsen, A.; Appelstrand, M.; Assembe-Mvondo, Samuel; Auld, G.; Hogl, K.; Humphreys, D.; Wildburger, C. (IUFRO, 2010)
From the existing full set of international policy instruments on forests, eight core components are identified and submitted to two differing assessments. The first (consistency assessment) uses a policy design approach to match the core omponents with their goals, policy tools, target group preferences and justifications for the choice of goals and policy tools. The second (compatibility assessment) examines the institutional inter-linkages of the core components. Both assessments reveal a series of challenges for international forest governance that can, however, be turned into opportunities. It is proposed that the coordination of and cooperation between the representatives of forest and non-forest users be strengthened at the national, regional and international levels, under the shared overarching idea of sustainable forest management, by means of ‘forests+’ policies. Forests+ policies go beyond the forest sector and acknowledge both the inter-sectoral character of forest policymaking and the importance of international regimes that have a decisive impact on forests but for which forests are not the main focus of attention.